2012
DOI: 10.1371/journal.pone.0042400
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cardiovascular and Renal Risk Is Associated with Low Nephron Endowment in Aged Females: An Ovine Model of Fetal Unilateral Nephrectomy

Abstract: Previously we have shown that ovariectomised (OVX) female sheep have reduced renal function and elevated blood pressure from 6 months of age following fetal uninephrectomy (uni-x) at 100 days of gestation (term  = 150 days). In the current study we examined if in intact female sheep the onset of decline in renal function and elevation in blood pressure was prevented. Studies were performed at 1 year, 2 and 5 years of age. Following fetal uni-x at 100 days, intact female sheep had ∼30% reduction in glomerular f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(42 citation statements)
references
References 66 publications
3
38
1
Order By: Relevance
“…At 5 months of age, all lambs underwent surgery, where the right carotid artery was exteriorized into a skin fold to form a carotid arterial loop [28], and following recovery the lambs were returned to pasture. As previously reported, at 1 and 2 years of age basal blood pressure and renal function were measured in these sheep [19]. At 5 years of age, female uni-x and sham animals were brought into the laboratory and placed in individual metabolic cages.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At 5 months of age, all lambs underwent surgery, where the right carotid artery was exteriorized into a skin fold to form a carotid arterial loop [28], and following recovery the lambs were returned to pasture. As previously reported, at 1 and 2 years of age basal blood pressure and renal function were measured in these sheep [19]. At 5 years of age, female uni-x and sham animals were brought into the laboratory and placed in individual metabolic cages.…”
Section: Methodsmentioning
confidence: 99%
“…All renal variables were corrected for body weight (bw). Kidney and body weights in this cohort of animals have been previously reported [19]. A two-tailed Student’s t test was used to compare basal differences between the sham and uni-x groups.…”
Section: Methodsmentioning
confidence: 99%
“…In the IUGR LPD females, it is possible that the initial congenital deficit combined with aging has markedly depleted renal functional reserve and, thus, counteracted the beneficial hormonal effects of circulating estrogen. In support of this idea, a congenital deficit in nephron number has been linked to an age-related decline in renal function in females in other animal programming models [including placental insufficiency (24,38), fetal uninephrectomy (54), and maternal nicotine (55)]. It has been suggested that kidneys with fewer nephrons are more sensitive to some stimuli (ANG II, renal ischemia reperfusion injury), which may increase their vulnerability to renal injury (23).…”
Section: Age-related Decline In Renal Function In Iugr and Non-iugr Mmentioning
confidence: 98%
“…However, this renal NO deficit is still very much evident in the 6-month old uni-x lambs. In terms of basal renal function, we have shown that renal blood flow declined in the uni-x sheep significantly between the age of 1 year to 5 years 25. Given the important role of NO in maintaining renal hemodynamics, such a decrease in renal function is consistent with a decline in NO levels with ageing.…”
Section: Discussionmentioning
confidence: 59%
“…The finding that our sheep with a congenital SFK have deficiencies in NO from as early as 6 months of age, a time when they are only very mildly hypertensive suggests this mechanism contributes to the overt and progressive elevations in blood pressure that occur with aging25. Having identified a deficiency of NO early in the disease phase, future studies can examine whether increasing NO bioavailability from this stage can be a viable treatment option for slowing the progression of disease in those with congenital SFK.…”
mentioning
confidence: 83%